Whole-genome sequencing and biofilm gene characterization in multidrug-Resistant Staphylococcus aureus clinical strains - Emira Noumi; Tarek Zmantar; Nouha Bouali; Abdulrahman S. Bazaid; Khulood Fahad Alabbosh; Kamel Chaieb; Hisham N. Altayb; Vincenzo De Feo; Mejdi Snoussi (Journal of Genetic Engineering and Biotechnology)
Staphylococcus aureus is known as a significant contributor to a variety of severe, life-threatening illnesses. Infectious diseases associated with biofilm-producing S. aureus can lead to a substantial increase in morbidity and mortality rates. This study aimed to characterize the whole genomes of eight clinically multidrug-resistant S. aureus strains isolated from several types of human infections sites from Hail Hospital, Saudi Arabia. Biofilm production was evaluated using Congo-red agar plates (CRA), polystyrene microtiter plate technique (MtP), and adherence to human epithelial cells (Hep 2). Additionally, adhesion to abiotic surface (Polyethylene, glass, stainless steel) was assessed using scanning electron microscopy (SEM). Then whole genome sequencing was conducted for all strains to analyze the virulome, resistome and phylogenome using different bioinformatic tools.Our results revealed that all S. aureus strains were slime producer on CRA plates with pigmented colonies (black and nearly black morphotypes) and were also able to form biofilm on the surface of several materials with different degrees. All tested strains adhere to Hep2 cell lines with a percentage of infected cells ranging from 45.0 % ± 0.078 to 92.0 % ± 0.022, and a total number of S. aureus/100 cells varying from 5.11 ± 2.14 (Strain S22) to 20.25 ± 5.15 (Strain S14). These results were correlated with those obtained from genome annotation highlighting that all multidrug resistant and biofilm-producing S. aureus strains harbored four ica genes (icaA, icaB, icaC, icaD) and their regulator icaR), clumping factor A and B (clfA and clfB genes), fibronectin binding proteins (fnbA in all strains and fnbB in 87.5 % of tested strains), elastin binding protein (ebps gene), extracellular adherence protein (Eap), staphylococcal protein A (spa gene), and Ser-Asp rich fibrinogen-binding proteins (sdrC). Most of the studied strains contained six to ten genomic islands associated with virulence factors, phage proteins, transcriptional regulators, insertion sequences and antimicrobial resistance genes. The study reported the presence of key adhesion-related genes underscores the colonization potential and pathogenicity in our strains. Additionally, the identification of multiple genomic islands associated with virulence and antimicrobial resistance highlights the need for vigilant monitoring in clinical settings.